(untitled) (Bangladesh Journal of Agricultural Research, 2009)
Onion bulbs of different sizes (20g, 15g and l0 g) were planted at different dates viz., 30 October and 15 and 30 November to observe their effects on growth, bulb and seed yield of onion. The mother bulb size and planting dates showed significant influence on growth, bulb and seed yield of onion. The large mother bulb and early planting were favourable for getting higher bulb and seed yields. The treatment combinations of large mother bulb (20 g) and 30 October planting time gave the highest bulb (17.52 t1ha) and seed (402.80 kg1ha) yield. Â Key words: Onion, mother bulb size, planting time, growth, yield. doi: 10.3329/bjar.v33i4.2285 Bangladesh J. Agril. Res. 33(4) : 531-537, December 2008 Â